Haemostatic radiation therapy for a bleeding intraductal papillary neoplasm of the biliary tree. Issue 1 (14th December 2018) - Sundaravadanan, Senthil; Mathew, Manu; Ram, Thomas Samuel; Joseph, Philip
Abstract : Haemostatic radiation was effectively used as a novel rescue therapy in a 60-year-old man who presented with recurrent melaena refractory to all conventional medical and surgical measures. He needed multiple transfusions and was diagnosed to be bleeding from an intraductal papillary biliary neoplasm which was not amenable to surgical resection in view of the background liver disease. He received conventional radiation therapy (RT) of a dose of 3 Gy per fraction for 3 consecutive days after which he stabilised. After cessation of the RT, he did not require transfusion for the next 2 months. His quality of life improved and it gave us time to evaluate for other definitive measures.